Relationship Between The Use of National Health Insurance Mobile Application and Health Services - Irmayani, Irmayani; Ginting, Rosita; Samura, Jul Asdar; Parinduri, Anggi; Bangun, Sri Melda; Dina Nuraini Hasanah (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2024)
Background: Advances in science and technology continue to develop rapidly, including in the use of the National Health Insurance (JKN) Mobile application. Mobile JKN is a digital innovation developed by BPJS Kesehatan. With this application, people can easily access comprehensive health services. Mobile JKN is a progressive step in ensuring equal access for everyone. In addition, users of this application can be more practical when forgetting to bring a physical card; Just open the application, the officer can view the card online. Objective: This study aims to explain the relationship between the use of the Mobile JKN application and the quality of health services. Research method: This study uses a quantitative method with an analytical survey approach and a cross-sectional design. The population in this study is all BPJS participants in the working area of the Pagar Merbau Health Center, Deli Serdang Regency. Samples were taken purposively, and primary and secondary data were collected for analysis. Results: The results showed that the majority of respondents (64.7%) used the Mobile JKN application, and the majority of respondents (70.4%) stated that the quality of health services they received was good. There was a significant relationship between the use of Mobile JKN and the quality of health services in the working area of the Pagar Merbau Health Center, Deli Serdang Regency (p=0.002). It is hoped that people in the Pagar Merbau Health Center area will make more use of the Mobile JKN application to get more effective and efficient services when receiving treatment. In addition, health workers are expected to continue to socialize about Mobile JKN on a regular basis, so that the public always remembers the importance of using this application to get optimal service.